Bridge deck and method of construction

CN122918937APending Publication Date: 2026-10-16CHONGQING UNIV OF ARTS & SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611379095.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]本发明的目的在于提供一种桥面板及施工方法,解决了现有ECC-NC复合结构的界面仅采用简单的凿毛处理,容易导致层间剥离、滑移失效的问题

Benefits of technology

[0018] The use of interfacial composite shear layers provides shear strength and anti-peeling ability higher than that of simple roughening treatment, in order to effectively reduce the risk of interlayer slippage or debonding failure of bridge decks under repeated vehicle loads, temperature changes or shrinkage deformation, thereby improving the bending and fatigue resistance of bridge decks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918937A_ABST
    Figure CN122918937A_ABST
Patent Text Reader

Abstract

The application discloses a bridge deck slab and a construction method, and relates to the technical field of bridge decks. The main technical scheme is as follows: a first structural layer, a second structural layer and an interface composite shear layer are provided, the first structural layer is made of concrete; the second structural layer is made of high ductility cement-based composite material, and the second structural layer is arranged on the lower surface of the first structural layer; and the interface composite shear layer is connected to the first structural layer and the second structural layer. The interface composite shear layer provides higher shear strength and anti-peeling capacity than simple chiseling treatment, so as to effectively reduce the risk of interlayer slip or debonding damage of the bridge deck slab under the action of repeated vehicle load, temperature change or shrinkage deformation, and further improve the bending resistance and fatigue resistance of the bridge deck slab.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of bridge deck technology, specifically to a bridge deck panel and its construction method. Background Technology

[0002] Normal concrete (NC) structures are prone to localized cracking and steel corrosion under complex external loads, and their durability gradually declines with service life. While engineered cementitious composites (ECCs) possess excellent mechanical and durability properties, their cost is 3-5 times that of NCs, becoming a major bottleneck restricting their large-scale application. To fully utilize the performance advantages of ECCs and control costs, current technologies combine ECCs and NCs to form ECC-NC composite structures. In such composite structures, the interface is a critical area for stress transfer. However, current ECC-NC composite structures only employ simple roughening treatment at the interface, easily leading to interlayer delamination and slip failure problems. Summary of the Invention

[0003] The purpose of this invention is to provide a bridge deck and construction method that solves the problem that the interface of the existing ECC-NC composite structure is only roughened by simple chiseling, which easily leads to interlayer peeling and slippage failure.

[0004] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:

[0005] In a first aspect, a bridge deck is provided, comprising a first structural layer, a second structural layer, and an interface composite shear layer, wherein the first structural layer is made of concrete; the second structural layer is made of a high-ductility cement-based composite material and is disposed on the lower surface of the first structural layer; and the interface composite shear layer is connected to the first structural layer and the second structural layer.

[0006] A further proposed solution is: an anti-shear groove is formed on the upper surface of the second structural layer; an anti-shear block is formed on the lower surface of the first structural layer; and the anti-shear block is adapted to fit within the anti-shear groove.

[0007] A further improvement is that the surface roughness Ra of the second structural layer is ≥1.5mm.

[0008] A further proposed solution is as follows: the interface composite shear layer includes a first reinforcing mesh, a second reinforcing mesh, and longitudinal connecting bars; the first reinforcing mesh is disposed within the first structural layer and is arranged along the width direction of the first structural layer; the second reinforcing mesh is disposed within the second structural layer and is arranged along the width direction of the second structural layer; the two ends of the longitudinal connecting bars are respectively connected to the first reinforcing mesh and the second reinforcing mesh; the number of longitudinal connecting bars is set to a plurality, and the plurality of longitudinal connecting bars are evenly distributed along the width and length directions of the first reinforcing mesh.

[0009] A further proposed solution is that the high-ductility cement-based composite material comprises 2% by volume polyvinyl alcohol fiber and 25% by volume recycled rubber powder.

[0010] A further proposed solution is that the second structural layer (2) has a 3-day compressive strength ≥31MPa, a 3-day tensile strength ≥4MPa, a 28-day compressive strength ≥43MPa, a 28-day tensile strength ≥6MPa, an ultimate tensile strain ≥3.6%, a crack width ≤60μm, an elastic modulus of 14.6~19.6GPa, and a 28-day self-healing efficiency ≥85%.

[0011] A further proposed solution is that the thickness ratio of the first structural layer to the second structural layer is 3:1 to 4:1.

[0012] In a second aspect, a construction method is provided, the construction method being applicable to bridge decks as described in the first aspect, the construction method comprising the following operations:

[0013] S1, prefabricated second structural layer; wherein, a shear groove is formed on the upper surface of the second structural layer, and an interface composite shear layer is provided on the second structural layer;

[0014] S2, Install the second structural layer onto the main beam;

[0015] S3, pour the first structural layer on the upper surface of the second structural layer and keep it moist for a preset time;

[0016] S4. Check whether the feature parameters meet the preset values. If yes, it is recorded as qualified; otherwise, it is recorded as unqualified.

[0017] Compared with the prior art, the beneficial effects of the present invention are:

[0018] The use of interfacial composite shear layers provides shear strength and anti-peeling ability higher than that of simple roughening treatment, in order to effectively reduce the risk of interlayer slippage or debonding failure of bridge decks under repeated vehicle loads, temperature changes or shrinkage deformation, thereby improving the bending and fatigue resistance of bridge decks. Attached Figure Description

[0019] Figure 1 This is a side view of a bridge deck structure in this embodiment;

[0020] Figure 2 This is a schematic diagram of the longitudinal section structure of a bridge deck in this embodiment.

[0021] The attached diagram shows the markings and corresponding component names:

[0022] 1-First structural layer; 2-Second structural layer;

[0023] 3-Interface composite shear layer; 31-First steel mesh; 32-Second steel mesh; 33-Longitudinal connecting bar. Detailed Implementation

[0024] The invention will now be further described with reference to the accompanying drawings.

[0025] Example 1: This example provides a bridge deck, such as... Figures 1-2 As shown, it includes a first structural layer 1, a second structural layer 2, and an interface composite shear layer 3. The first structural layer 1 is made of concrete; the second structural layer 2 is made of high-ductility cement-based composite material and is disposed on the lower surface of the first structural layer 1; the interface composite shear layer 3 connects the first structural layer 1 and the second structural layer 2.

[0026] For example, in the implementation process, the first structural layer 1 is made of concrete (NC) with a strength grade of C40~C50, and the thickness of the first structural layer 1 is 4 / 5 to 3 / 4 of the bridge deck thickness (i.e., the thickness of the first structural layer 1 + the thickness of the second structural layer 2). The second structural layer 2 is made of high-ductility cementitious composite material (ECC), and the thickness of the second structural layer 2 is 1 / 5 to 1 / 4 of the bridge deck thickness (i.e., the thickness of the first structural layer 1 + the thickness of the second structural layer 2). The first structural layer 1, the interface composite shear layer 3, and the second structural layer 2 are arranged sequentially from top to bottom, and the upper and lower ends of the interface composite shear layer 3 are connected to the first structural layer 1 and the second structural layer 2, respectively. The interface composite shear layer 3 can be formed by using shear connectors (such as steel trusses, corrugated steel plates), embedded shear fiber mesh, etc., to form a composite force transmission mechanism of mechanical interlocking and chemical bonding, so as to reduce the risk of delamination or slippage between the first structural layer 1 and the second structural layer 2 under complex loads.

[0027] During use, the first structural layer 1 serves as the upper surface of the bridge deck, bearing the compressive stress generated by vertical loads and providing overall stiffness and bridge deck flatness; the second structural layer 2 serves as the lower surface of the bridge deck and completely covers the positive bending moment tension zone of the bridge deck. By utilizing the high ductility, fine crack control capability, and impermeability of the second structural layer 2, the ability to resist tensile stress on the bottom surface is improved and the risk of corrosive media such as chloride ions entering is reduced.

[0028] In this embodiment, the bridge deck utilizes an interfacial composite shear layer 3 to provide shear strength and peel strength higher than that of simple roughening treatment. This aims to effectively reduce the risk of interlayer slippage or debonding failure of the bridge deck under repeated vehicle loads, temperature changes, or shrinkage deformation, thereby improving the bending and fatigue resistance of the bridge deck.

[0029] In this embodiment, an anti-shear groove is formed on the upper surface of the second structural layer 2; an anti-shear block is formed on the lower surface of the first structural layer 1; the anti-shear block is adapted to fit within the anti-shear groove.

[0030] For example, during implementation, a shear groove (not shown in the figure) is formed on the upper surface of the second structural layer 2. The shape of the shear groove can be trapezoidal, rectangular, semi-circular, dovetail-shaped, or other geometric shapes that can provide mechanical interlocking. For instance, after the second structural layer 2 is cast and hardened (or pre-formed in the mold during casting), a series of regularly or irregularly arranged grooves, i.e., shear grooves, are formed on the upper surface of the second structural layer 2. The groove depth is 6~10mm, the groove width is 10~15mm, and the distance between two adjacent shear grooves is 100~150mm.

[0031] Shear blocks (not shown in the figure) are formed on the lower surface of the first structural layer 1. For example, when the first structural layer 1 is poured onto the upper surface of the second structural layer 2, fresh concrete flows into the shear groove on the second structural layer 2 and, after hardening, forms protrusions that match the shape of the shear groove, i.e., shear blocks. The shear blocks and the shear groove fit tightly together, forming a concave-convex interlocking structure. The aim is to provide large-scale geometric interlocking through the cooperation of the shear groove and the shear block, and to provide microscopic interlocking by utilizing the roughness between the shear groove and the shear block, thereby increasing the coefficient of friction and chemical bonding area of ​​the contact surface.

[0032] In this embodiment, the bridge deck utilizes the geometric interlocking between shear blocks and shear grooves to constrain the relative displacement of the first structural layer 1 and the second structural layer 2 in the horizontal direction. When the bridge deck is subjected to vehicle loads, temperature changes, or shrinkage deformation, the interfacial shear stress is transmitted through the lateral compression and friction of the concave-convex structure, thereby significantly improving the shear strength and reducing the risk of interlaminar slip failure.

[0033] In this embodiment, the roughness Ra of the upper surface of the second structural layer 2 is ≥1.5mm.

[0034] For example, during implementation, the surface roughness Ra of the upper surface of the second structural layer 2 is ≥1.5mm. For instance, after the second structural layer 2 has hardened, the upper surface of the second structural layer 2 can be treated by methods such as sandblasting, high-pressure water jetting, steel brush roughening, or light chiseling to ensure that the surface roughness Ra of the upper surface of the second structural layer 2 is ≥1.5mm; or, when casting the second structural layer 2, a template with a rough texture (such as a sand mold or indentation film) can be used to ensure that the surface roughness Ra of the hardened upper surface of the second structural layer 2 is ≥1.5mm; or, a shear groove can be pre-reserved on the upper surface of the second structural layer 2, and then the surfaces between the shear grooves and the inner surface of the shear grooves can be roughened to ensure that the surface roughness Ra of the upper surface of the second structural layer 2 is ≥1.5mm.

[0035] During use, the anti-shear groove and anti-shear block work together to provide large-scale geometric locking; the roughness provides micro-interlocking to increase the coefficient of friction and chemical bonding area of ​​the contact surface.

[0036] In this embodiment, the bridge deck utilizes the surface roughness Ra≥1.5mm of the second structural layer 2 to effectively increase the actual contact area between the first structural layer 1 and the second structural layer 2, while simultaneously improving the mechanical interlocking and friction coefficient between the first structural layer 1 and the second structural layer 2. This aims to generate stronger resistance under shear loads, thereby further enhancing shear strength.

[0037] In this embodiment, the interface composite shear layer 3 includes a first reinforcing mesh 31, a second reinforcing mesh 32, and longitudinal connecting bars 33; the first reinforcing mesh 31 is disposed within the first structural layer 1 and is arranged along the width direction of the first structural layer 1; the second reinforcing mesh 32 is disposed within the second structural layer 2 and is arranged along the width direction of the second structural layer 2; the two ends of the longitudinal connecting bars 33 are respectively connected to the first reinforcing mesh 31 and the second reinforcing mesh 32; the number of longitudinal connecting bars 33 is set to a plurality, and the plurality of longitudinal connecting bars 33 are evenly distributed along the width and length directions of the first reinforcing mesh 31.

[0038] For example, in the implementation process, the above-mentioned interface composite shear layer 3 includes a first steel mesh 31, a second steel mesh 32, and longitudinal connecting bars 33. The first steel mesh 31 is disposed inside the first structural layer 1 and is arranged along the width direction of the first structural layer 1, that is, the length direction of the first steel mesh 31 is the same as the length direction of the first structural layer 1, and the width direction of the first steel mesh 31 is the same as the width direction of the first structural layer 1.

[0039] The second steel mesh 32 is disposed inside the second structural layer 2 and arranged along the width direction of the second structural layer 2. That is, the length direction of the second steel mesh 32 is the same as the length direction of the second structural layer 2, and the width direction of the second steel mesh 32 is the same as the width direction of the second structural layer 2.

[0040] The two ends of the longitudinal connecting bars 33 are connected to the first reinforcing mesh 31 and the second reinforcing mesh 32 respectively by binding, welding, or snap-fitting. Several longitudinal connecting bars 33 are provided, evenly distributed along the width and length directions of the first reinforcing mesh 31. The longitudinal connecting bars 33 are made of Φ8~Φ12 ribbed steel bars, and the spacing between two adjacent longitudinal connecting bars 33 along the length direction and the width direction of the first reinforcing mesh 31 is 200mm, resulting in a 200mm×200mm square grid arrangement. Simultaneously, the lower end of the longitudinal connecting bar 33 extends into the second structural layer 2 to a depth ≥10d (d is the diameter of the longitudinal connecting bar 33), and the upper end of the longitudinal connecting bar 33 extends into the first structural layer 1 to a depth ≥15d. When the thickness of the second structural layer 2 is less than 10d, the lower end of the longitudinal connecting bar 33 can be bent within the second structural layer 2; when the thickness of the first structural layer 1 is less than 15d, the upper end of the longitudinal connecting bar 33 can be bent within the first structural layer 1.

[0041] In the process of use, the first step is to prefabricate the second structural layer 2 in the factory. First, install the formwork for the second structural layer 2, then tie the required second reinforcing mesh 32 inside the formwork, and tie and weld longitudinal connecting bars 33 onto the second reinforcing mesh 32. Next, construct a high-ductility cement-based composite material inside the formwork, and perform mechanical vibration and manual smoothing. Then, steam cure the second structural layer 2 for 3 days at a temperature of 23±2℃ and humidity ≥90% to ensure that the strength of the second structural layer 2 reaches 70% of the design value. Finally, shear grooves are opened on the upper surface of the second structural layer 2, and the surface roughness Ra of the upper surface of the second structural layer 2 is made ≥1.5mm.

[0042] The second step is to install the second structural layer 2 onto the main beam. First, a truck crane is used to hoist the second structural layer 2 onto the steel / concrete main beam, and then shear members (such as PBL connectors or weld studs) are used to reliably connect the second structural layer 2 to the main beam. Next, the flatness is corrected (deviation ≤ 3mm / m), and anti-overturning supports are installed.

[0043] The third step involves pouring the first structural layer 1 onto the upper surface of the second structural layer 2 and maintaining it with moisture for a predetermined curing time. First, the required first reinforcing mesh 31 inside the first structural layer 1 is tied or welded to the upper end of the longitudinal connecting bars 33. Next, a support structure (with a bearing capacity ≥ 1.2 times the self-weight of the first structural layer 1) is erected on the upper surface of the second structural layer 2. Then, concrete of strength grade C40~C50 is poured onto the upper surface of the second structural layer 2 (using continuous pouring with layer thickness ≤ 300mm), and compacted using an immersion tamper (vibration time 20~30s / point). Finally, geotextile is covered on the first structural layer 1 and water is sprayed for moisture maintenance for no less than 7 days.

[0044] The fourth step is to check whether the characteristic parameters meet the preset values. If yes, it is recorded as qualified; otherwise, it is recorded as unqualified. After the strength of the first structural layer 1 reaches 80% of the design value, the bridge deck is formed. At this time, the characteristic parameters of the bridge deck, such as the interfacial bond strength, flexural bearing capacity, and crack width, are checked. When the interfacial bond strength ≥ 2.5 MPa, the flexural bearing capacity ≥ 1.1 times the design value, and the crack width ≤ 40 μm, all are met, the bridge deck is recorded as qualified and can be put into use; when at least one of the following is not met, the bridge deck is recorded as unqualified.

[0045] In this embodiment, the bridge deck utilizes longitudinal connecting ribs 33 that directly penetrate the interface to resist shear slippage between the first structural layer 1 and the second structural layer 2. The two ends of the longitudinal connecting ribs 33 are anchored to the first reinforcing mesh 31 and the second reinforcing mesh 32, respectively, forming a spatial force system to effectively transmit shear force. Simultaneously, the longitudinal connecting ribs 33 are subjected to normal tensile stress to improve the interface's anti-peeling performance, thereby reducing the risk of interface peeling.

[0046] In a preferred embodiment, the surfaces of the first reinforcing mesh 31, the second reinforcing mesh 32, and the longitudinal connecting bars 33 are all coated with an epoxy resin coating (coating thickness ≥ 0.15 mm). This is intended to further enhance corrosion resistance and form a dual protection with the impermeability of the second structural layer 2.

[0047] In a preferred embodiment, there are two first steel meshes 31, which are arranged sequentially from top to bottom, with a spacing of 150~200mm between them and a protective layer thickness of ≥30mm, which is suitable for the conventional reinforcement requirements of steel-concrete composite beam bridge deck.

[0048] In this embodiment, the high-ductility cement-based composite material comprises 2% by volume polyvinyl alcohol fiber and 25% by volume recycled rubber powder.

[0049] For example, in the implementation process, the above-mentioned high-ductility cement-based composite material is made by mixing polyvinyl alcohol fiber, recycled rubber powder, cement, fly ash, silica sand, high-efficiency water-reducing agent, and early-strength agent in a specific ratio. Specifically, the volume content of polyvinyl alcohol fiber is 2%, the diameter of the polyvinyl alcohol fiber is 39 μm, the length of the polyvinyl alcohol fiber is 12 mm, the tensile strength of the polyvinyl alcohol fiber is 1620 MPa, the elastic modulus is 42.8 GPa, and the elongation is 7%; the volume content of recycled rubber powder is 25%.

[0050] In this embodiment, the bridge deck uses 2% polyvinyl alcohol fiber by volume, which provides more stable crack bridging capability, making the material exhibit strain hardening and multi-crack characteristics, thereby increasing the ultimate tensile strain capacity of the second structural layer 2. Simultaneously, using 25% recycled rubber powder by volume as flexible particles significantly reduces the elastic modulus of the second structural layer 2 and improves the strain hardening behavior of the material during stress, absorbing more fracture energy. Furthermore, the addition of 25% recycled rubber powder by volume to the material used in the second structural layer 2 achieves the resource utilization of solid waste (consuming 53 kg of waste tire rubber powder per cubic meter of the second structural layer 2), meeting the requirements of "green, low-carbon, energy-saving, and environmentally friendly" (reducing carbon emissions by ≥15%), thus possessing both economic and ecological value.

[0051] In a preferred embodiment, the elastic modulus of the first structural layer 1 is 30~40 GPa; the elastic modulus of the second structural layer 2 is 14.6~19.6 GPa. This aims to achieve stress matching at the composite cross-section of the first structural layer 1 and the second structural layer 2, thereby ensuring a planar cross-section.

[0052] In this embodiment, the second structural layer 2 has a 3-day compressive strength ≥31MPa, a 3-day tensile strength ≥4MPa, a 28-day compressive strength ≥43MPa, a 28-day tensile strength ≥6MPa, an ultimate tensile strain ≥3.6%, a crack width ≤60μm, an elastic modulus of 14.6~19.6GPa, and a 28-day self-healing efficiency ≥85%. This aims to improve the early strength of the second structural layer 2 to adapt to rapid industrial construction (achieving lifting strength within 3 days). Simultaneously, it aims to extend the bridge deck's service life by ≥50% (from 60 years to over 90 years) and increase fatigue life by ≥3 times (to adapt to millions of wheel loads).

[0053] In this embodiment, the performance indicators of the high-ductility cement-based composite material used for the second structural layer 2 are compared with those of existing high-ductility cement-based composite materials, as shown in Table 1:

[0054] Table 1

[0055] 3-day compressive strength (MPa) 25±1.2 31±1.5 Increased by 24% 28-day compressive strength (MPa) 45±2.0 43±1.8 A 4.4% decrease (sacrificing slight compressive strength for ductility) 3-day tensile strength (MPa) 3.2±0.2 4.0±0.2 Increase by 25% 28-day tensile strength (MPa) 5.8±0.3 6.0±0.3 Increased by 3.45% 3-day ultimate tensile strain (%) 2.8±0.1 4.0±0.1 An increase of 42.9% 28-day ultimate tensile strain (%) 1.8±0.1 (attenuation 35.7%) 3.61±0.1 (attenuation 9.75%) The ductility decay rate decreased by 72.7%. Crack width (μm) after 28 days 80~100 ≤60 Reduce ≥25% 28-day self-healing rate (%) 60±5 85±5 An increase of 41.7%

[0056] In this embodiment, the thickness ratio of the first structural layer 1 to the thickness of the second structural layer 2 is 3:1 to 4:1.

[0057] For example, in the implementation process, the thickness of the first structural layer 1 is 4 / 5 to 3 / 4 of the bridge deck thickness (i.e., the thickness of the first structural layer 1 + the thickness of the second structural layer 2), and the thickness of the second structural layer 2 is 1 / 5 to 1 / 4 of the bridge deck thickness (i.e., the thickness of the first structural layer 1 + the thickness of the second structural layer 2).

[0058] Example 1:

[0059] First structural layer 1 (C40~C50): Thickness 170~240mm (±2mm), flatness deviation ≤3mm / m

[0060] Second structural layer 2: 30~80mm (±2mm) thick, containing 25% recycled rubber powder by volume and 2.0% polyvinyl alcohol fiber by volume. The upper surface of the second structural layer 2 has a gradient roughness, with a groove depth of 10mm (±1mm) in the tension zone and 6mm (±1mm) in the non-tension zone, and a surface roughness Ra=1.5~2.0mm.

[0061] The rectangular shear groove on the upper surface of the second structural layer 2: the groove depth is 6~10mm (±1mm), the groove width is 10~15mm (±1mm), the shear grooves are arranged in a matrix, the transverse spacing of the shear grooves is 100~150mm (±5mm), the longitudinal spacing is 100~150mm (±5mm), and the shear grooves are filled with the first structural layer 1 (C40~C50 concrete).

[0062] Interface composite shear layer 3: Interface composite shear layer 3 includes two first steel meshes 31, one second steel mesh 32, and longitudinal connecting bars 33. Among them, the first steel meshes 31 are made of Φ12~Φ16 ribbed steel bars, the transverse spacing of the steel bars on the first steel meshes 31 is 150~200mm (±5mm), the longitudinal spacing of the steel bars on the first steel meshes 31 is 150~200mm (±5mm), and the two first steel meshes 31 are arranged in parallel in the first structural layer 1 along the direction from the upper surface to the lower surface. The distance between the upper first steel mesh 31 and the upper surface of the first structural layer 1 is 30mm (±2mm), and the distance between the lower first steel mesh 31 and the lower surface of the first structural layer 1 is 30mm (±2mm). The second reinforcing mesh 32 uses ribbed steel bars of Φ8~Φ10. The transverse spacing of the steel bars on the second reinforcing mesh 32 is 200mm (±5mm), and the longitudinal spacing of the steel bars on the second reinforcing mesh 32 is 200mm (±5mm). The second reinforcing mesh 32 is set inside the second structural layer 2, and the second reinforcing mesh 32 is located at the upper 1 / 3 of the second structural layer 2 (10~27mm away from the upper surface of the second structural layer 2). The longitudinal connecting bars 33 are made of Φ8~Φ12 ribbed steel bars. The transverse spacing of the longitudinal connecting bars 33 is 200mm (±5mm), and the longitudinal spacing of the longitudinal connecting bars 33 is 200mm (±5mm). The center of the longitudinal connecting bars 33 is offset from the center of the shear groove by ≤20mm. The upper end of the longitudinal connecting bars 33 extends into the first structural layer 1 to a depth ≥15d (d is the diameter of the longitudinal connecting bar 33), and the lower end of the longitudinal connecting bars 33 extends into the second structural layer 2 to a depth ≥10d. The welding length of the longitudinal connecting bars 33 to the first steel mesh 31 and the second steel mesh 32 is ≥10d (using manual arc welding, weld height ≥6mm, free of porosity and slag inclusions). The outer surfaces of the first steel mesh 31, the second steel mesh 32, and the longitudinal connecting bars 33 are all coated with epoxy resin, and the thickness of the epoxy resin coating is ≥0.15mm, with a coating continuity of ≥95%. When the thickness of the second structural layer 2 is less than 10d, the lower end of the longitudinal connecting bar 33 can be bent within the second structural layer 2; when the thickness of the first structural layer 1 is less than 15d, the upper end of the longitudinal connecting bar 33 can be bent within the first structural layer 1.

[0063] The neutral axis of the bridge deck formed by the first structural layer 1 and the second structural layer 2 is located 60~96mm from the upper surface of the second structural layer 2 (which is 1 / 3~1 / 2.5 of the bridge deck thickness). The tension zone is the second structural layer 2 (covering a length ≥ 1 / 3 of the span), and the compression zone is the first structural layer 1.

[0064] Protective layer thickness: First structural layer 1 ≥ 30 mm (± 2 mm), second structural layer 2 ≥ 20 mm (± 2 mm).

[0065] Example 2:

[0066] Bridge deck: 240mm thick.

[0067] Second structural layer 2: 50mm thick (mixed with 25% recycled rubber powder), 3-day compressive strength 31MPa, 3-day tensile strength 4MPa, 28-day compressive strength 43MPa, 28-day ultimate tensile strain 3.61%, crack width ≤40μm. The shear grooves on the upper surface of the second structural layer 2 are rectangular (with a groove depth of 8mm, a groove width of 12mm, and a spacing of 120mm between adjacent shear grooves). The upper surface of the second structural layer 2 is a gradient rough surface (10mm depth in the tensile zone, 6mm depth in the non-tensile zone, roughness Ra=1.8mm).

[0068] First structural layer 1: 190mm thick, strength grade C50 (28-day compressive strength 50MPa, 28-day tensile strength 4.1MPa).

[0069] Interface composite shear layer 3: Second reinforcing mesh 32 Φ8 steel bars @ 200mm (arranged 17mm above the second structural layer 2), first reinforcing mesh 31 Φ14 steel bars @ 180mm (one first reinforcing mesh 31 is 30mm from the top surface of the first structural layer 1, and the other first reinforcing mesh 31 is 30mm from the interface), longitudinal connecting bars 33 Φ10 @ 200mm × 200mm (the upper end extends 170mm into the first structural layer, and the lower end extends 20mm into the second structural layer, welded). When the thickness of the second structural layer 2 is less than 20mm, the lower end of the longitudinal connecting bars 33 can be bent within the second structural layer 2; when the thickness of the first structural layer 1 is less than 170mm, the upper end of the longitudinal connecting bars 33 can be bent within the first structural layer 1.

[0070] Applicable scenarios: Small and medium span (20~40m) highway steel-concrete composite beam bridges, prefabricated second structural layer 2 and interface composite shear layer 3, and cast-in-place first structural layer 1, construction without scaffolding, suitable for heavy traffic (axle load ≥130kN).

[0071] Example 3:

[0072] Bridge deck: 280mm thick.

[0073] Second structural layer 2: 60mm thick (mixed with 25% recycled rubber powder), covering the entire tension zone under negative bending moment (length = 1 / 3 of the span = 8m), with a 28-day ultimate tensile strain of 3.61% and a crack width ≤ 40μm. The shear grooves on the upper surface of the second structural layer 2 are rectangular (with a groove depth of 10mm, a groove width of 15mm, and a spacing of 100mm between adjacent shear grooves), and the surface roughness Ra of the upper surface of the second structural layer 2 is 2.0mm.

[0074] First structural layer 1: 220mm thick, strength grade C45 (28-day compressive strength 45MPa, 28-day tensile strength 3.8MPa).

[0075] Interface composite shear layer 3: Second steel mesh 32 Φ10 steel bars @ 200mm (arranged 20mm above the second structural layer 2), first steel mesh 31 Φ16 steel bars @ 150mm (one first steel mesh 31 is 30mm from the top surface of the first structural layer 1, and the other first steel mesh 31 is 30mm from the interface), longitudinal connecting bar 33 Φ12 @ 200mm × 200mm (the upper end extends 195mm into the first structural layer, and the lower end extends 25mm into the second structural layer, and is welded).

[0076] Advantages: No through cracks in the negative bending moment zone, elimination of transverse prestressing (saving 15% of the cost), simplified construction, fatigue resistance improved by ≥3 times, and subsequent maintenance costs reduced by ≥60%.

[0077] Example 4:

[0078] Bridge deck: 200mm thick.

[0079] Second structural layer 2: 30mm thick (mixed with 25% recycled rubber powder), with a 3-day compressive strength of 31MPa, suitable for rapid construction stress requirements (reaching hoisting strength within 3 days). The upper surface of the second structural layer 2 is roughened (groove depth 6mm, roughness Ra=1.5mm).

[0080] First structural layer 1: 170mm thick, strength grade C40 (28-day compressive strength 40MPa, 28-day tensile strength 3.5MPa).

[0081] Interface composite shear layer 3: Second steel mesh 32 Φ8 steel bars @ 200mm (arranged 10mm above the second structural layer 2), first steel mesh 31 Φ12 steel bars @ 200mm (one first steel mesh 31 is 30mm from the top surface of the first structural layer 1, and the other first steel mesh 31 is 30mm from the interface), longitudinal connecting bar 33 Φ8 @ 200mm × 200mm (the upper end extends 145mm into the first structural layer, and the lower end extends 12mm into the second structural layer, and is welded).

[0082] Advantages: Lightweight design (self-weight 25kN / m², 15% lower than conventional concrete bridge deck), adaptable to the dynamic performance requirements of light rail bridges (natural frequency ≥5Hz), crack width controlled within ≤60μm, self-healing ability, and durability improved by ≥50% (design service life ≥100 years).

[0083] Example 2: This example provides a construction method applicable to bridge decks as described in Example 1. The construction method includes the following operations:

[0084] S100. Prefabricate the second structural layer 2; wherein, the upper surface of the second structural layer 2 is provided with a shear groove, and an interface composite shear layer 3 is provided on the second structural layer 2;

[0085] For example, during implementation, firstly, the template for the second structural layer 2 is installed (dimensional deviation ±2mm), and a release agent is applied. Next, the required second reinforcing mesh 32 is tied inside the template, and longitudinal connecting bars 33 (spacing deviation ±5mm, weld height ≥6mm) are tied and welded onto the second reinforcing mesh 32. Then, a high-ductility cement-based composite material is constructed inside the template, and mechanical vibration and manual smoothing are performed. Next, the second structural layer 2 is steam-cured for 3 days at a temperature of 23±2℃ and humidity ≥90% to ensure that the strength of the second structural layer 2 reaches 70% of the design value. Then, shear grooves are opened on the upper surface of the second structural layer 2, and the surface roughness Ra of the upper surface of the second structural layer 2 is made ≥1.5mm.

[0086] S200. Install the second structural layer 2 onto the main beam;

[0087] For example, during implementation, a truck crane (lifting speed ≤ 0.5 m / s, levelness deviation ≤ 3 mm / m) is first used to hoist the second structural layer 2 onto the steel / concrete main beam, and the second structural layer 2 is reliably connected to the main beam using shear members (such as PBL connectors or weld studs) (overturning resistance coefficient ≥ 1.5, weld height ≥ 8 mm). Next, the flatness is corrected (deviation ≤ 3 mm / m), and anti-overturning supports are installed (spacing between anti-overturning supports ≤ 2 m).

[0088] S300. Cast the first structural layer 1 on the upper surface of the second structural layer 2 and keep it moist for a preset time;

[0089] For example, during implementation, firstly, the required first steel mesh 31 inside the first structural layer 1 is tied or welded to the upper end of the longitudinal connecting bar 33 (welding length ≥ 10d, protective layer thickness ≥ 30mm ± 2mm). Secondly, a support frame (bearing capacity ≥ 1.2 times the self-weight of the first structural layer 1) is erected on the upper surface of the second structural layer 2 to support the pouring of the first structural layer 1. Next, concrete with a strength grade of C40~C50 is poured on the upper surface of the second structural layer 2 (slump 100~120mm, continuous pouring, layer thickness ≤ 300mm), and compacted using an immersion tamper (vibration time 20~30s / point). Finally, geotextile is covered on the first structural layer 1 and cured with water (humidity ≥ 90%) for no less than 7 days (strength ≥ 80% of design value).

[0090] S400. Check whether the detection feature parameters meet the preset values. If yes, record it as qualified; otherwise, record it as unqualified.

[0091] For example, during implementation, the characteristic parameters are checked to see if they meet preset values. If yes, it is recorded as qualified; otherwise, it is recorded as unqualified. After the strength of the first structural layer 1 reaches 80% of the design value, the bridge deck is formed. At this time, the characteristic parameters of the bridge deck, such as the interfacial bond strength, flexural bearing capacity, and crack width, are checked. When the interfacial bond strength ≥ 2.5 MPa, the flexural bearing capacity ≥ 1.1 times the design value, and the crack width ≤ 40 μm, all are satisfied, the bridge deck is recorded as qualified and can be put into use; when at least one of the following is not satisfied, the bridge deck is recorded as unqualified.

[0092] In this embodiment, the second structural layer 2 is prefabricated in the factory and serves as the permanent bottom formwork on the construction site. This aims to eliminate the need for additional formwork support and dismantling procedures, thereby shortening the construction period by ≥30% (from 15 days to 10 days for a single span). This adapts to the rapid construction requirements of steel-concrete composite beam bridges, reduces on-site wet work (lowering environmental impact), and improves construction efficiency and quality stability (factory prefabrication quality pass rate ≥98%).

[0093] Although the invention has been described herein with reference to several illustrative embodiments, it should be understood that many other modifications and implementations can be devised by those skilled in the art, which will fall within the scope and spirit of the principles disclosed herein. More specifically, various variations and modifications can be made to the components and / or layout of the subject matter arrangement within the scope of the disclosure, drawings, and claims. Besides variations and modifications to the components and / or layout, other uses will be apparent to those skilled in the art.

Claims

1. A bridge deck, characterized in that, include: The first structural layer (1) is made of concrete; The second structural layer (2) is made of a high-ductility cement-based composite material and is disposed on the lower surface of the first structural layer (1). An interface composite shear layer (3) is connected to the first structural layer (1) and the second structural layer (2).

2. The bridge deck according to claim 1, characterized in that: The upper surface of the second structural layer (2) is provided with shear grooves; Shear blocks are formed on the lower surface of the first structural layer (1); The shear-resistant block is adapted to the shear-resistant groove.

3. The bridge deck according to claim 2, characterized in that: The roughness Ra of the upper surface of the second structural layer (2) is ≥1.5mm.

4. The bridge deck according to claim 3, characterized in that: The interface composite shear layer (3) includes a first steel mesh (31), a second steel mesh (32), and longitudinal connecting bars (33); The first steel mesh (31) is disposed in the first structural layer (1), and the first steel mesh (31) is arranged along the width direction of the first structural layer (1); The second steel mesh (32) is disposed within the second structural layer (2), and the second steel mesh (32) is arranged along the width direction of the second structural layer (2); The two ends of the longitudinal connecting bar (33) are respectively connected to the first steel mesh (31) and the second steel mesh (32); The longitudinal connecting bars (33) are provided in a plurality of quantities, and the plurality of longitudinal connecting bars (33) are evenly distributed along the width and length directions of the first steel mesh (31).

5. The bridge deck according to claim 1, characterized in that: The high-ductility cement-based composite material comprises 2% by volume polyvinyl alcohol fiber and 25% by volume recycled rubber powder.

6. The bridge deck according to claim 1, characterized in that: The second structural layer (2) has a 3-day compressive strength ≥31MPa, a 3-day tensile strength ≥4MPa, a 28-day compressive strength ≥43MPa, a 28-day tensile strength ≥6MPa, an ultimate tensile strain ≥3.6%, a crack width ≤60μm, an elastic modulus of 14.6~19.6GPa, and a 28-day self-healing efficiency ≥85%.

7. The bridge deck according to claim 1, characterized in that: The thickness ratio of the first structural layer (1) to the thickness of the second structural layer (2) is 3:1 to 4:

1.

8. A construction method, characterized in that, The construction method is applicable to bridge decks as described in any one of claims 1 to 7, and the construction method includes the following operations: S1, prefabricated second structural layer (2); wherein, the upper surface of the second structural layer (2) is provided with shear groove, and the second structural layer (2) is provided with interface composite shear layer (3); S2, install the second structural layer (2) onto the main beam; S3, pour the first structural layer (1) onto the upper surface of the second structural layer (2) and keep it moist for a preset time; S4. Check whether the feature parameters meet the preset values. If yes, it is recorded as qualified; otherwise, it is recorded as unqualified.